2007 IEEE International Conference on Image Processing 2007
DOI: 10.1109/icip.2007.4379843
|View full text |Cite
|
Sign up to set email alerts
|

On the Resolution Limits of Superimposed Projection

Abstract: Multi-projector super-resolution is the dual of multi-camera superresolution. The goal of projector super-resolution is to produce a high resolution frame via superimposition of multiple low resolution subframes. Prior work claims that it is impossible to improve resolution via superimposed projection except in specialized circumstances. Rigorous analysis has been previously restricted to the special case of uniform display sampling, which reduces the problem to a simple shift-invariant deblurring. To understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…Theoretical questions around the possibility of super-resolution have been clearly resolved; more details on the theoretical aspects of superimposed projection may be found in [5,6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical questions around the possibility of super-resolution have been clearly resolved; more details on the theoretical aspects of superimposed projection may be found in [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…In recent work [5,6], we showed that in fact superresolution via superimposed projection is theoretically possible even in the case of non-uniform sampling. Specifically, we can generate subframes that are themselves severely aliased, but when superimposed combine to form alias-free high resolution images.…”
Section: Introductionmentioning
confidence: 98%
“…The fixed overlay approach has been referred to by numerous terms including superimposed projection [24] / superimposed displays [25], optical pixel sharing [26], and display supersampling [27]. This approach is exemplified by the work of Jaynes and Ramakrishnan's [12] using multiple projectors and Heide, et al's [13] and Lanman, et al's [14,15] demonstration of stacked LCD panels).…”
Section: Fixed Overlay-based Approachesmentioning
confidence: 97%
“…Prior work on overlaid coloration sources has included the use of optical pixel sharing [23], display super-sampling [24], and superimposition techniques for projectors [25] and conventional displays [26]. Techniques that incorporate movement have also been developed.…”
Section: Display Enhancementmentioning
confidence: 99%